Crisis of the Greeks (the euro crisis) and the lessons learned - عبد خضير ايمان; عبد المجيد خالد عبد الحميد (Journal of Economics and Administrative Sciences, 2013)
After more than ten years of successful march of the European single currency and EU countries faced a crisis in one of its debt, which recently joined the monetary union is not Greece . Perhaps mpre than th effects of this crisis, the fact that its consequences were not confined to Greece alone , but expand it to include all EU countries in general and the countries of the European Monetary Union in particular. Sine the debt crisis that emerged Greek and talk a lot a bout their effects on the global economy and the potential harm done th the situation of the global economy recovers from the global financial crisis (mortgage crisis), or delayed and also the fears of other crises to other member states sufer from a deficit in the payment of government debts such as Portugal, lreland and spain. I have shaken confidence (in euros) of the puppies , and the crisis cast a burden on the European central bank and the governments of member states in the region, monetary and difficult task tedious, since one of the first main tasks has is to remove the specter of violent shocks and crises of acute and mitigate its impact and its impact on the economies of the monetary union (EU). That the Greek crisis was behind a defect in the monetary union (EU), representing the conditions of joining the monetary union, especially on the side of fiscal policy, and a number of factors internal to the Greek economy and the rush to join the monetary union, EU to take advantage of the benefits from monetary union and not to give costs to the importance that required and must reserve before the foot to enter the monetary union,. And external standards and because of the conditions that forced reece to implement them in addition to international factors.